IMPLEMENTASI PENDIDIKAN NILAIDALAM MATA KULIAH DASAR UMUM (MKDU)(STUDI KASUS PADA JURUSAN MKDU-FPIPS-UPI - Rahmdani,, Dani (2004)
Theoretically, MKDU as values education has a purpose to complete education which emphasizes intellectual quotient (IQ), with emotional quotient (EQ) and spiritual quotient (SQ) to generate an excellent bachelor: capable in reasoning, emoting and spiritualizing to become a good citizen. From a pilot study, it is known that the implementation of Values Education within MKDU still put the emphasis to merely transfer of knowledge that requires only factual judgment. This research has a purpose to study some problems in the application of values education within MKDU, and also to generate theories through findings derived from data analysis and generalizations. Owing to the vast scope of phenomenon under study, this research is limited merely to the subjects which are included to Personality Development Subjects (MPK), and from an in depth considerations the focus of the research is generated as follows: 1) the messages of values carried out within MKDU, 2) lecturer's perspectives on values education, 3) the implementation of values education, 4) factors influencing the implementation of values education. Values education concerns with moral and non-moral considerations of any objects; including ethics and aesthetics. The objectives of values education is to help students to explore the existence values through critical judgment so that he will be able to improve the quality of his reasoning and also his emotion. Values education at least encompasses four dimensions, those are: 1) the identification the personal and social core values; the philosophy and rational findings of those core values; emotional and afectual respond upon those core values; the decision making concerning those values based on such findings and responds. Values education such as "values conflict" equips students with an opportunity to verify and clarify their own values and exploring alternative solutions to improve students' capacity in making a responsible and fair decision. This study uses single analytical model throughout the whole study-a qualitative case study-and this model was applied as an in depth examination of some specific problems concerning the implementation of values education within MKDU. This study uses three main techniques in collecting data: interview, participant observation, and document analysis. To analyze the data two strategies were applied: general and operational strategies. The general strategy was done by synchronizing the data with the correlative assumptions underpinning values education. Whereas operational strategy was done by applying two techniques of analysis simultaneously ("Modified Analytic Induction" & "Constant Comparative Method"). Both strategies were done with a purpose to keep the consistency of the study and also to come to the most valid and reliable data. The most important findings of this study are that Values Education puts too much emphasis on student's cognitive achievement rather than the balance between their intellectual (IQ), emotional (EQ), and spiritual quotient (SQ) at once. The process of valuing (emoting and spiritualizing) is not occurred within values education.